Serum Chemerin Levels Correlate With Determinants of Metabolic Syndrome in Obese Children and Adolescents. (June 2019) - Ba, Hong-Jun; Xu, Ling-Ling; Qin, You-Zhen; Chen, Hong-Shan
Objectives: This study aimed to investigate serum chemerin concentrations in obese children and adolescents and to investigate the associations of chemerin with body mass index (BMI), lipid levels, and insulin sensitivity. Methods: Forty-eight obese and 40 nonobese Chinese children and adolescents were included in the study. BMI and levels of chemerin, lipids, glucose, and insulin were measured following an overnight fast. The Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) and BMI standard deviation score (BMI-SDS) were determined for all participants. Results: Serum chemerin levels were found to be significantly higher in obese children and adolescents than in control group members (94.83 ± 5.99 ng/mL vs 56.43 ± 4.16 ng/mL, P < .001). There were significant correlations between chemerin and age, BMI, BMI-SDS, total triglyceride (TG) levels, insulin levels, and HOMA-IR. After controlling for age, we found that chemerin levels were also significantly correlated with BMI-SDS (r =+ 0.284, P = .008) and HOMA-IR (r =+ 0.241, P = .034). In a stepwise multiple regression analysis, we observed only BMI-SDS to be an important determinant of chemerin level. Conclusions: In our sample of Chinese children and adolescents, chemerin levels were significantly higher in the obese group than in the control group. Chemerin levels were positively correlated with BMI-SDS and HOMA-IR and negatively correlated with age. We thus believe that further study is necessary to investigate the risk of metabolic abnormalities in young obese children and adolescents.